Easy Office 2016 : see it done, do it yourself - Rutledge, Patrice-Anne (Indianapolis, Indiana : Que, 2016)
Easy Office 2016 teaches students the fundamentals to help them get the most from Office 2016. Fully illustrated steps with simple instructions guide them through each task, building the skills they need to make the most of the new features and tools of Office 2016.
Part I. Microsoft Office 2016. Getting started with Microsoft Office 2016 -- Working with Office applications -- Working with text -- Working with pictures -- Working with shapes, SmartArt, and screenshots -- Using Microsoft Office on the Web and mobile devices -- Part II. Microsoft Word 2016. Creating a document in Microsoft Word -- Enhancing Word documents -- Controlling page layout -- Reviewing and viewing Word documents -- Part III. Microsoft Excel 2016. Creating an Excel workbook -- Formatting worksheet data -- Working with cell formulas and functions -- Working with charts, Pivot Tables, and Sparklines -- Part IV. Microsoft PowerPoint 2016. Creating and managing PowerPoint presentations -- Editing and formatting presentations -- Working with audio, video, and animation -- Reviewing and making presentations -- Part V. Microsoft Outlook 2016. Sending and receiving messages -- Organizing and scheduling in Outlook -- Part VI. Microsoft OneNote 2016. Creating notebooks -- Enhancing and managing notebooks -- Part VII. Microsoft Publisher 2016. Creating publications -- Enhancing and managing publications.
Includes index.
Keywords: Microsoft Office; Microsoft Word; Microsoft Excel (Computer file); Microsoft PowerPoint (Computer file); Microsoft Publisher; Microsoft Outlook; Microsoft Excel (Computer file); Microsoft Office; Microsoft Outlook; Microsoft PowerPoint (Computer file); Microsoft Publisher; Microsoft Word; Business -- Computer programs; Business -- Computer programs